No interaction between factor V Leiden and hyperhomocysteinemia or MTHFR 677TT genotype in venous thrombosis - Keijzer, Miranda B. A. J.; Borm, George F.; Blom, Henk J.; Bos, Gerard M. J.; Rosendaal, Frits R.; den Heijer, Martin (Thrombosis and Haemostasis, 2007)
Homocysteine may have a thrombogenic effect through inhibition of inactivation of factor Va by activated protein C. Because factor V Leiden also leads to resistance of factor V to activated protein C, it would be possible that both factors show interaction for the risk of venous thrombosis. This has been reported in some studies, but not in others. We performed a meta-analysis to investigate a possible interaction between factor V Leiden and hyperhomocysteinemia, including 825 subjects with venous thrombosis and 2,109 controls, for the risk of venous thrombosis. In addition, we assessed a possible interaction between factor V Leiden and MTHFR 677TT genotype (the most common genetic determinant of homocysteine levels), including 2,547 subjects with venous thrombosis and 4,327 controls. We also investigated the interaction effect of factor V Leiden and hyperhomocysteinemia in a large case-only study using data of the VITRO study, including 2,077 subjects with first-time venous thrombosis. The meta-analysis yielded no evidence for additive or multiplicative interaction between factor V Leiden and hyperhomocysteinemia [relative excess risk due to interaction (RERI) –1.77 (95%CI –8.61 to 5.08) and multiplicative interaction term 0.86 (95%CI 0.35 to 2.14)].The case-only study also showed no interaction effect [0.58 (95%CI 0.29 to 1.16)]. Also the metaanalysis on factor V Leiden and MTHFR 677TT yielded no evidence of interaction; RERI 0.13 (95%CI –3.60 to 3.86) and multiplicative interaction term 1.23 (95%CI 0.72 to 2.11). Both the meta-analyses of published studies and a large case-only study did not show evidence for interaction between factor V Leiden and hyperhomocysteinemia for risk of venous thrombosis.
Keywords: MTHFR; Methylenetetrahydrofolatereductase; homocysteine; factor V Leiden; meta-analysis; case-only; case-control; VITRO